PUBLIC SHOPPING MOTIVATION MODEL TO SUPERMARKET - Helmi, Arief; Lestari, Nenni Heksa (Jurnal Ekonomi dan Bisnis Terapan, 2018)
As the increasing preferences of Indonesian people to shop at supermarket encourage this investigation to uncover underlying motivation of the preferences. Consumer survey was conducted with questionnaires with closed questionnaires of 22 initial factors that were predicted to be shopping motivation. The Confirmation Factor Analysis (CFA) was carried out on the survey data, and resulted in eight new factors formulated into Models Shopping Motivation to Supermarket. This model shows the eight motivations that drive consumer to shop at supermarket: cheap prices, fun or shopping entertainment, shopping convenience, shopping pleasure, togetherness with friends, and enjoy atmosphere appeal. These results confirm that consumer's motivation to shop at supermarkets rather than at traditional markets is hedonic motivation.